Significado de humanização da assistência para os profissionais de saúde que atendem na sala de emergência de um pronto-socorro - Mercia Aleide Ribeiro Leite (2010)
This study is an attempt to understand the meaning given to the term humanization of hospital attendance by health professionals who work in emergency rooms on a daily basis, and how they use the understanding of this amongst them and towards the patient during the first clinical assessment. This led the author to interact with five health professionals who work in this environment and, in order to put this into practice, comprehensive sociology issues were used, with references to Alfred Schütz, Maffesoli and some ideas of Erving Goffman and Marcel Mauss. The work of understanding human issues in the emergency room was divided into six chapters: the first describes the authors concerns with the proposal; the second depictures the theoretical background used in the study and articulates with the method used in research; the third, the methodology used in the study; the fourth describes the theoretical concepts of humanism, humanization and dehumanization; the fifth is subdivided into six parts: the "face to face" relation between professionals in emergency room, being gifted and good and evil, corporal technique: the humanizing factor in the emergency room, be a community in the emergency room; the tribe in the emergency room; Hospital Infrastructure: contributions to human and non-human; spirituality and pain in the emergency room. In each part, we tried to understand and interpret the phenomenon. The sixth chapter is an invitation to restart understanding the concepts surrounding humanization on the emergency setting